Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2147/ppa.s142556
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three types of central venous catheters in patients with malignant tumor receiving chemotherapy

Abstract: BackgroundCentral venous catheters (CVCs) have been an effective access for chemotherapy instead of peripherally intravenous catheters. There were limited studies on the choices and effects of different types of CVCs for chemotherapy. The aim of this study was to compare the complications, cost, and patients’ quality of life and satisfaction of three commonly used CVCs for chemotherapy, such as implanted venous port, peripherally inserted central catheters (PICCs), and external non-tunneled central venous cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 27 publications
(43 reference statements)
4
88
1
6
Order By: Relevance
“…81,83,90 In eight studies, 80,[82][83][84][86][87][88]90 clinical signs prompted ultrasonic or radiological testing to diagnose VTE; the other three studies did not report the trigger for VTE testing. 81,85,89 VTEs were diagnosed by venography in two studies, 82,88 ultrasound in four, 80,83,84,86 and various methods (venography, CT, and magnetic resonance imaging) in two. 87,90 Two studies noted use of anticoagulant prophylaxis.…”
Section: The Ors Of Tivap-associated Vtementioning
confidence: 99%
“…81,83,90 In eight studies, 80,[82][83][84][86][87][88]90 clinical signs prompted ultrasonic or radiological testing to diagnose VTE; the other three studies did not report the trigger for VTE testing. 81,85,89 VTEs were diagnosed by venography in two studies, 82,88 ultrasound in four, 80,83,84,86 and various methods (venography, CT, and magnetic resonance imaging) in two. 87,90 Two studies noted use of anticoagulant prophylaxis.…”
Section: The Ors Of Tivap-associated Vtementioning
confidence: 99%
“…An aspect of IVAD that is often overlooked and rarely evaluated is the effect of the device on the patient's quality of life. Studies show that patients who have port‐CVCs report a higher quality of life when compared to patients with TCVCs . Port‐CVCs are completely localized under the skin, which allows patients to bathe and swim without the need for occlusive dressings.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Studies show that patients who have port-CVCs report a higher quality of life when compared to patients with TCVCs. 43,44 Port-CVCs are completely localized under the skin, which allows patients to bathe and swim without the need for occlusive dressings. Maintenance of port-CVCs with monthly line flushes is simpler than that for TCVCs, which require regular dressing changes and weekly line flushes.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Several complications, such as infections, can be associated with the insertion of a central access device (Moell et al, ). Patients with an SVP have fewer complications than patients with a CVC (Coady, Ali, Sidloff, Kenningham, & Ahmed, ; Fang, Yang, Song, Jiang, & Liu, ) and also report a higher quality of life than those with a CVC (Fang et al, ). By contrast, Flynn, Willis, Gaur, and Shenep () showed that there is a greater risk of recurring catheter‐related infections with an SVP than with a CVC.…”
Section: Introductionmentioning
confidence: 99%